Aerodynamic evaluation of wing shape and wing orientation in four butterfly species using numerical simulations and a low-speed wind tunnel, and its implications for the design of flying micro-robots. Issue 1 (6th February 2017) - Ortega Ancel, Alejandro; Eastwood, Rodney; Vogt, Daniel; Ithier, Carter; Smith, Michael; Wood, Rob; Kovač, Mirko
Abstract : Many insects are well adapted to long-distance migration despite the larger energetic costs of flight for small body sizes. To optimize wing design for next-generation flying micro-robots, we analyse butterfly wing shapes and wing orientations at full scale using numerical simulations and in a low-speed wind tunnel at 2, 3.5 and 5 m s −1 . The results indicate that wing orientations which maximize wing span lead to the highest glide performance, with lift to drag ratios up to 6.28, while spreading the fore-wings forward can increase the maximum lift produced and thus improve versatility. We discuss the implications for flying micro-robots and how the results assist in understanding the behaviour of the butterfly species tested.